2014
DOI: 10.1007/s11250-014-0641-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of management practices and animal age on incidence of mastitis in Nili Ravi buffaloes

Abstract: Buffalo is an economically important dairy animal in South Asia but mostly ignored in research priorities. In this retrospective study, the effect of management practices and age of animal on the incidence of mastitis in Nili Ravi buffaloes was investigated. A total of 1,560 quarters of buffaloes (n = 390) were screened by visual examination of the udder and milk (clinical mastitis) and California mastitis test (subclinical mastitis). Household data was collected on a predesigned questionnaire and analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
22
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 20 publications
6
22
1
2
Order By: Relevance
“…Interestingly, the majority of ESBL-producing E. coli (23 isolates) were recovered from herds in Inner Mongolia province possibly linked to dense farming (2.37 million dairy cows) with the largest dairy herds in this province (Dou, 2014). Dense farming is significantly correlated with the incidence of bovine mastitis (Ali et al, 2014), and mastitis is the main reason for frequent and prolonged use of antibiotics that exert selective pressure for emergence and dissemination of resistant isolates (Berge et al, 2005). Our results revealed that CTX-M, mainly the CTX-M-15, was the most prevalent genotype, followed by TEM and SHV.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the majority of ESBL-producing E. coli (23 isolates) were recovered from herds in Inner Mongolia province possibly linked to dense farming (2.37 million dairy cows) with the largest dairy herds in this province (Dou, 2014). Dense farming is significantly correlated with the incidence of bovine mastitis (Ali et al, 2014), and mastitis is the main reason for frequent and prolonged use of antibiotics that exert selective pressure for emergence and dissemination of resistant isolates (Berge et al, 2005). Our results revealed that CTX-M, mainly the CTX-M-15, was the most prevalent genotype, followed by TEM and SHV.…”
Section: Discussionmentioning
confidence: 99%
“…Çetin and Alan [35] encountered mastitis cases in 125 right front, 113 right rear, 116 left fronts and 125 left rear udder lobes of cows. Ali et al [36] found clinical mastitis cases in right front mammary lobes of buffaloes at a rate of 19.29%, 26.32% in right rear mammary lobes, 12.28% in left front mammary lobes and 34.21% in left rear mammary lobes.…”
Section: Discussionmentioning
confidence: 98%
“…The present study also evaluated the risk factors associated with bovine tuberculosis and concluded that the large herd size (usually ≥10 animals) substantially involved in the high prevalence rate of disease. Moreover, the managemental practices are more difficult in larger herds as compared to smaller herd sizes and ultimately have more possibilities for transmission and spreading of infectious diseases (Ali et al, 2014). A larger herd size of animals has a significantly positive impact of diseases on animal health (Bilal et al, 2004;Ali et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the managemental practices are more difficult in larger herds as compared to smaller herd sizes and ultimately have more possibilities for transmission and spreading of infectious diseases (Ali et al, 2014). A larger herd size of animals has a significantly positive impact of diseases on animal health (Bilal et al, 2004;Ali et al, 2014). Similarly, milk yield of dairy animals showed significant effects on disease occurrence.…”
Section: Discussionmentioning
confidence: 99%